Concepção(ões) de texto em contexto de EaD semipresencial - Komesu, Fabiana Cristina [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
By following the example proposed by Corrêa (2011) in the investigation of texts produced by undergraduate and pre-undergraduate students in two different assessment, this work aims to approach “hidden” aspects in the teaching of writing at the university (Street, 2009), to reflections produced in the language field, in particular the ones referred as “socially assumed”, proposed by Voloshinov/Bakhtin (s/d: 1926). It is particularly important to investigate the conception of text in digital context, by means of the study of updated semiotic resources in the production of undergraduate students using a computer with internet access in the process of semi-present Distance Learning (DL). The collected material comprises 29 (twenty nine) texts which were produced by students of the semipresent Pedagogy Course from Univesp (Universidade Virtual do Estado de São Paulo – Virtual University from the state of São Paulo), who were studying “Education and Language”, in 2010. This qualitative analysis aims to show that regarding the institution there is a prevalence of structural and procedural aspects for the accomplishment of the proposed activity and, regarding the undergraduate student it is noticed that the production is characterized by a traditional conception of text, mainly recognized by written verbal text, although the proposal prioritized the relation between verbal and non verbal language. Regarding discursive-linguistic studies, it is important to reflect about a text conception that privileges the integration of multiple semiosis by taking into account the socio-historical interlocution character established within utterances of others.

A exemplo do que propõe Corrêa (2011) na investigação de textos produzidos por universitários e pré-universitários em duas diferentes situações de avaliação, procuro, neste trabalho, aproximar aspectos “ocultos” no ensino de escrita na universidade (Street, 2009) de reflexões produzidas no âmbito dos estudos da linguagem, em particular, aquelas propostas por Voloshinov/Bakhtin (s/d: 1926) no que se refere à noção de “presumido social”. Interessa-me, de maneira particular, investigar concepção(ões) de texto em contexto digital, por meio do estudo de recursos semióticos atualizados na produção do universitário que utiliza computador com acesso à internet no processo de Educação a Distância (EaD) semipresencial. O conjunto do material é formado de 29 (vinte e nove) textos produzidos por alunos do Curso Pedagogia semipresencial da Univesp (Universidade Virtual do Estado de São Paulo), disciplina “Educação e Linguagem”, no ano de 2010. A análise, de cunho qualitativo, procura mostrar que, do ponto de vista da instituição, há prevalência de aspectos estruturais e procedimentais nas instruções para realização da proposta da atividade; do ponto de vista do universitário, observa-se que a produção é caracterizada por concepção tradicional de texto, reconhecida, principalmente, por texto verbal escrito, embora a proposta priorizasse relação entre linguagem verbal e não verbal. Do ponto de vista dos estudos linguístico-discursivos, proponho refletir sobre uma concepção de texto que privilegie a integração entre múltiplas semioses, considerando-se o caráter de interlocução sócio-histórica estabelecido com enunciados alheios.
Text conception(s) in context of semi-present Distance Learning (DL)
Keywords: escrita; universitário; educação a distância; writing; undergraduate; distance learning